If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + b = 50 Solving 45 + b = 50 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-45' to each side of the equation. 45 + -45 + b = 50 + -45 Combine like terms: 45 + -45 = 0 0 + b = 50 + -45 b = 50 + -45 Combine like terms: 50 + -45 = 5 b = 5 Simplifying b = 5
| 11x-14=-113 | | (3x-7)=(2x+3) | | -48=-9-13m | | 147-4x=79 | | 4xn=32 | | (3x-7)+(2x+3)=180 | | 23=4y+5 | | 12x-11x+5=-(x+3)+5 | | 189-y=272 | | (3x+7)=(2x+3) | | (x*5)-x=600 | | 216=-u+129 | | 2(3)+3y=5 | | .0001/125 | | 2845=48x-563 | | 4x-2=2x+36 | | 4(2a+5)+4=3(5a-6) | | 22x+81=147 | | 0=12-5lnx | | 66x+339=2715 | | 24+32p=x | | 2x+5x-3=9 | | 66x+339=2719 | | 5x-73=117 | | 36+5x=91 | | 16r^2-r=0 | | 5a-10-3a=4a-a+16-3a | | 2x^3-4x^2+3x+9=0 | | (2-6)(3-6)=70 | | (x+1)(x-5)+5=0 | | 12u-6u=36 | | a=-2b+-3c |